Selection of Material and Manufacturing Technology for Batik Canting Stamps Based on Multi-Criteria Decision-Making Methods - Joni Setiawan; Andi Sudiarso; Isananto Winursito; Muhammad Kusumawan Herliansyah (Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
This study aimed to develop alternative materials and technologies for making canting stamps used in producing batik canting (stamped batik) to transfer hot wax from the pan to the fabric. Previous researchers have studied materials such as wood, aluminum, multiplex, acrylic, and acrylonitrile butadiene styrene (ABS). Manufacturing technologies have also been analyzed, including manual manufacturing, computer numerical control (CNC) milling, laser cutting, and additive manufacturing. However, none of these materials and technologies were considered suitable alternatives for copper canting stamps. This paper proposes Conductive ABS-Electroformed By Copper (CABS-EBC) through additive manufacturing and electroforming processes as alternative material for canting stamps. A multi-criteria decision-making (MCDM) approach was used to assess alternative materials and technologies. The alternatives and criteria were calculated using the Simple Additive Weighting (SAW), Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS), and Preference Ranking Organization Method of Enrichment Evaluation (PROMETHEE) techniques. Besides this, assessment was also carried out based on expert opinions. The results showed that copper was the most suitable material, with Closeness = 1.000, Yi = 0.995, and Phi = +1.00. Meanwhile, CABS-EBC ranked second, with Closeness = 0.627, Yi = 0.864, and Phi = +0.50. The selected technology was additive manufacturing combined with electroforming, with Closeness = 0.700, Yi = 0.895, and Phi = +0.39. By using MCDM on the material-technology development candidates it was found that CABS-EBC processed with additive manufacturing is capable of substituting copper as a canting stamp material. It is expected that the production capacity of the traditional manufacturing process can be enhanced by adopting these new materials and technologies.